Pengaruh Gaya Hidup, Kualitas Produk, dan Citra Merek terhadap Pembelian Kosmetik Maybelline di Kota Yogyakarta - Sari Listiana; Eka Sudarusman (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2023)
This research aims to determine the influence of lifestyle, product quality and brand image on purchasing decisions for Maybelline cosmetics in the city of Yogyakarta. The population of this study were Maybelline cosmetics users in the city of Yogyakarta and its surroundings. Sampling was carried out using Non-Probability Sampling with purposive sampling technique. The total sampling was 100 respondents. The results of this study indicate that lifestyle has no influence on purchasing decisions for Maybelline cosmetics in the city of Yogyakarta. Meanwhile, product quality and brand image have a positive and significant influence on purchasing decisions for Maybelline cosmetics in the city of Yogyakarta.